Simulasi CFD Pengaruh Konsentrasi Nanofluida Al2O3/Air Terhadap Performa Perpindahan Panas Pipa Radiator - Wicaksono, Yoga Arob; ., Sudarno; Suffiadi Akhmad, Nanang (Jurnal Energi Dan Manufaktur, 2020)
The performance of heat transfer on a car radiator can be improved by using nanofluids as working fluids. In this study analyzes the of heat transfer performance of Al 2 O 3 /water nanofluids that pass through cylindrical pipes in 3D using the CFD simulation method for single phase approach. This research studied the effect of nanofluid concentration  0.1, 0.5, 1 and 1.5% on the heat transfer coefficient. The Reynolds number is varied between 9000 to 23000 and the ambient temperature is constant. The results showed that 1.5% Al 2 O 3 /water nanofluid increasing heat transfer coefficient up to 5.7% compared to base fluid.